Electrode, preparation method thereof and battery

By adopting a double-layer conductive structure in the electrode, including coating the second conductive layer on the surface of the active material layer and overlapping the empty foil area of ​​the first conductive layer, the problem of large electron transport impedance of the electrode is solved, and the energy density and charging efficiency of the battery are significantly improved.

CN119764329APending Publication Date: 2025-04-04CHINA AUTOMOTIVE BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510011331.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the electron transmission impedance of the electrodes is large, resulting in a decrease in battery power, and the problem is more prominent in high-power operation.

Method used

A high-face capacity electrode is designed, which adopts a double-layer conductive structure, including a first conductive layer, an active material layer and a second conductive layer. The second conductive layer is continuously coated on the surface of the active material layer and overlaps and overlaps in the empty foil region of the first conductive layer to form a composite conductive layer.

Benefits of technology

Through this design, the internal resistance of the battery is reduced to 23-34.8mΩ, the energy density is increased to 101%-131%, and the constant current ratio of the IC charging is increased to 73.8%-88.3%, which significantly improves the internal resistance and power performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764329A_ABST
    Figure CN119764329A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode, a preparation method thereof and a battery, and belongs to the technical field of batteries. The electrode comprises a first conductive layer, an active material layer and a second conductive layer, wherein the active material layer is clamped between the first conductive layer and the second conductive layer; the surface of the first conductive layer is divided into an active coating area and an empty foil area adjacent to one side of the active coating area; active material layers are respectively attached to two opposite surfaces of the active coating area; the empty foil area is divided into a first empty foil area close to the active material layer and a second empty foil area far away from the active material layer; the second conductive layer is continuously attached to the surface, away from the first conductive layer, of the active material layer, the side wall, close to the empty foil area, of the active material layer and the surface of the first empty foil area. By adopting the high-surface-capacity double-layer conductor electrode designed by the invention, the internal resistance of the battery is reduced to 23-34.8 m omega, the energy density is improved to 101%-131%, the IC charging constant current ratio is improved to 73.8%-88.3%, and the improvement effect is obvious.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrode and a preparation method thereof, and a battery. Background Art

[0002] Against the backdrop of increasingly severe global environmental and energy issues, the development of new energy industries is considered an important strategic move. With people's yearning for a better life, countries around the world have formulated technical roadmaps for improving battery energy density and improved comprehensive performance in combination with scenario requirements. On the one hand, the development of electrode materials is still advancing, and on the other hand, optimizing battery structure design based on the existing material system has also received more attention. For example, the proposal of high-area capacity electrode structure gives the existing electrode material system a higher energy density. High-area capacity electrodes usually face problems such as poor mechanical properties and slow reaction kinetics. The electron transmission path is too long due to the thick active coating on the side away from the current collector, which ultimately leads to high battery resistance, poor power, and short life.

[0003] The prior art records a positive electrode sheet including a current collector and a first electrode material layer and a second electrode material layer sequentially arranged on one side of the current collector; the conductive agent in the first electrode material layer is a first conductive agent, the conductive agent in the second electrode material layer is a second conductive agent, and the conductivity of the first conductive agent is greater than the conductivity of the second conductive agent. In this technology, the same active material is compounded with different conductive agents, and the difference in slurry uniformity causes a new interlayer interface, which affects the transmission of electrons and ions.

[0004] The prior art records a positive electrode sheet including: a current collector; a first active material layer including a first active material; and a second active material layer; wherein the first active material layer is disposed between the current collector and the second active material layer, the first active material layer includes a first active material, and the first active material is selected from at least one of a modified ternary positive electrode material and a modified lithium iron phosphate. In this technology, the two active material layers have different slurries, and the differences in film formation and rolling increase the interlayer interface, which affects the transmission of electrons and ions.

[0005] The current public technology has alleviated the ion transport problem of high areal capacity electrodes to a certain extent. However, in actual engineering design, the slurry coating technology of materials of different particle sizes is difficult and has high manufacturing costs. It also has little effect on the electron transfer impedance problem in high areal capacity electrodes and cannot effectively overcome the electron transfer in high areal capacity electrodes. The problem is more prominent when the battery is working at high power. Summary of the invention

[0006] The main purpose of the present application is to provide an electrode and a preparation method thereof and a battery to solve the problems of large electron transfer impedance in the electrode and poor battery power in the prior art.

[0007] In order to achieve the above-mentioned object, according to one aspect of the present application, an electrode is provided, comprising: a first conductive layer, an active material layer, and a second conductive layer, wherein the active material layer is sandwiched between the first conductive layer and the second conductive layer; the surface of the first conductive layer is divided into an active coating area and a hollow foil area adjacent to one side of the active coating area; the active material layer is attached to each of two opposite surfaces of the active coating area;

[0008] Among them, the empty foil area is divided into a first empty foil area close to the active material layer and a second empty foil area away from the active material layer; the second conductive layer is continuously attached to the surface of the active material layer away from the first conductive layer, the side wall of the active material layer close to the empty foil area and the surface of the first empty foil area.

[0009] Furthermore, the material of the first conductive layer is conductive metal.

[0010] Furthermore, the material of the second conductive layer is a non-metallic conductive material.

[0011] Furthermore, the second empty foil area is a tab connection area.

[0012] Furthermore, the outer contours of the first conductive layer, the active material layer, the second conductive layer, and the empty foil area are in a square shape.

[0013] Further, a vertical connection line between two opposite sides of the first conductive layer divides the surface area of ​​the first conductive layer into an active coating area and a blank foil area.

[0014] Furthermore, the thickness of the second conductive layer attached to the surface of the active material layer is 1 to 7 micrometers.

[0015] Furthermore, the thickness of the second conductive layer attached to the surface of the first empty foil area is 1 to 10 microns.

[0016] Furthermore, the height of the second conductive layer attached to the surface of the first empty foil area is 100-200 microns.

[0017] Furthermore, the thickness of the first conductive layer is 1 to 30 micrometers.

[0018] Furthermore, the thickness of the active material layer is 30 to 100 micrometers.

[0019] Furthermore, the thickness of the second conductive layer attached to the surface of the active material layer is 1 to 5 micrometers.

[0020] Furthermore, the thickness of the second conductive layer attached to the surface of the first empty foil area is 5 to 10 microns.

[0021] Furthermore, the height of the second conductive layer attached to the surface of the first empty foil area is 100-150 microns.

[0022] Furthermore, the thickness of the first conductive layer is 1 to 20 micrometers.

[0023] Furthermore, the thickness of the active material layer is 50 to 65 micrometers.

[0024] Furthermore, the thickness of the second conductive layer attached to the surface of the active material layer is 1 to 3 micrometers.

[0025] Furthermore, the thickness of the second conductive layer attached to the surface of the first empty foil area is 5 to 8 microns.

[0026] Furthermore, the height of the second conductive layer attached to the surface of the first empty foil area is 100-120 microns.

[0027] Furthermore, the thickness of the first conductive layer is 4 to 13 micrometers.

[0028] Furthermore, the material of the first conductive layer is selected from one or more of conductive metals, composites of conductive metals and polymers, and alloys of conductive metals; wherein the conductive metal is selected from aluminum, copper, or nickel.

[0029] Furthermore, the material of the second conductive layer is selected from one or more of conductive carbon black, conductive graphite multi-walled carbon nanotubes, single-walled carbon nanotubes, vapor-grown carbon fibers, graphene, and conductive carbon microspheres.

[0030] Furthermore, the active material of the active material layer includes positive electrode active material or negative electrode active material; the positive electrode active material includes one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, nickel cobalt aluminum manganese oxide, lithium-rich manganese and lithium manganese oxide materials; the negative electrode active material includes one or more of graphite, silicon oxygen carbon, silicon carbon and nano silicon.

[0031] Furthermore, the electrode is a positive electrode and / or a negative electrode; the surface capacity of the positive electrode is greater than or equal to 2.0 mAh / cm 2 ; The surface capacity of the negative electrode is greater than or equal to 2.2 mAh / cm 2 .

[0032] Furthermore, the electrode is a positive electrode and / or a negative electrode; the surface capacity of the positive electrode is 3.5 to 5.5 mAh / cm 2 ; The surface capacity of the negative electrode is 3.85~5.95mAh / cm 2 .

[0033] According to the second aspect of the present application, a method for preparing the above-mentioned electrode is provided, the method comprising:

[0034] Step 1: applying the electrode slurry to two opposite surfaces of the active coating area of ​​the first conductive layer respectively to form an active material layer; wherein the area on the surface of the first conductive layer not coated with the electrode slurry is a blank foil area;

[0035] Step 2: Continuously apply the second conductive paste to the surface of the active material layer away from the first conductive layer, the side wall of the active material layer close to the empty foil area, and the surface of the first empty foil area to form a second conductive layer; wherein the area of ​​the empty foil area close to the active material layer is the first empty foil area, and the area not coated with the second conductive paste is the second empty foil area.

[0036] According to a third aspect of the present application, a battery cell is provided, wherein the electrode of the battery cell is the above-mentioned electrode or the electrode obtained by the above-mentioned preparation method.

[0037] According to a fourth aspect of the present application, a battery is provided, wherein the battery cell is the above-mentioned battery cell.

[0038] Furthermore, the operating current of the battery is not less than 1C operating current.

[0039] Furthermore, the internal resistance of the battery is 23-34.8 mΩ.

[0040] According to a fifth aspect of the present application, there is provided an electrical device comprising the above-mentioned battery.

[0041] Furthermore, electrical equipment includes mobile phones, new energy vehicles, unmanned aircraft, energy storage equipment, etc.

[0042] By applying the technical solution of the present application, an electrode and a preparation method thereof and a battery are provided. The electrode has a high surface capacity, and its electronic conductor adopts a double-layer structure design, a second conductive layer is arranged on the surface of the active material layer, and the first electronic conductive layer and the second electronic conductive layer intersect and overlap at the electrode hollow foil, and the active material layer is arranged between the first conductor layer and the second conductor layer. The internal resistance of the battery using the high surface capacity double-layer conductor electrode designed by the present application can be reduced to 23-34.8 mΩ, the energy density can be increased to 101%-131%, the IC charging constant current ratio can be increased to 73.8%-88.3%, and the internal resistance and battery power are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0044] Figure 1 A schematic diagram of the surface structure of the active material layer coated in Example 1 of the present application is shown;

[0045] Figure 2 A schematic diagram of the electrode surface structure of Example 1 of the present application is shown;

[0046] Figure 3 A schematic diagram of the side structure of the electrode in Example 1 of the present application is shown;

[0047] Figure 4 A schematic diagram of the side structure of an electrode in Comparative Example 1 of the present application is shown;

[0048] Figure 5 A schematic diagram of the side structure of the electrode of Comparative Example 5 of the present application is shown.

[0049] Reference numerals:

[0050] 1. Electrode;

[0051] 2. first conductive layer; 21. active coating area; 22. empty foil area; 221. first empty foil area; 222. second empty foil area;

[0052] 3. Active material layer;

[0053] 4. The second conductive layer; 41. The second conductive layer to which the active material layer is attached; 42. The second conductive layer to which the first empty foil area is attached. DETAILED DESCRIPTION

[0054] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0055] Traditional high-areal capacity electrodes have large electron transfer impedance, resulting in a serious drop in battery power. In order to reduce the internal resistance of the electrode and increase the battery power, this application designs a high-areal capacity electrode with a double-layer conductor structure.

[0056] like Figures 1 to 3 As shown, the structure of the electrode 1 of the present application includes: a first conductive layer 2, an active material layer 3 and a second conductive layer 4, wherein the active material layer 3 is sandwiched between the first conductive layer 2 and the second conductive layer 4; the surface of the first conductive layer 2 is divided into an active coating area 21 and a hollow foil area 22 adjacent to one side of the active coating area 21; the active material layer 3 is attached to each of the two opposite surfaces of the active coating area 21 of the first conductive layer 2, and the active material layer is not attached to the hollow foil area;

[0057] Among them, the empty foil area 22 is divided into a first empty foil area 221 (height such as 100 μm) close to the active material layer and a second empty foil area 222 (height such as 10 mm) away from the active material layer; the second conductive layer 4 is continuously attached to the surface of the active material layer 3 away from the first conductive layer 2, the side wall of the active material layer 3 close to the empty foil area 22 and the surface of the first empty foil area 221.

[0058] In the above-mentioned electrode structure of the present application, the first conductive layer 2 is also the current collector, and an active coating area and an empty foil area are arranged on the surface of the current collector. The empty foil area is often used in structures such as the tab, and this design is a conventional structure. The outer contour of the first conductive layer 2, the active material layer 3, the second conductive layer 4, and the empty foil area 22 is a square; the current collector is a square foil, and a vertical connecting line or a nearly vertical connecting line between two opposite sides (generally the long sides) on the foil divides the current collector into two areas, one side of the connecting line is the active coating area, and the other side of the connecting line is the empty foil area 22, such as Figure 1 The structure shown.

[0059] In the description of the electrode structure of this application, the surface of the first conductive layer 2 is divided into an active coating area 21 and a hollow foil area 22 adjacent to one side of the active coating area 21; in this description, the active coating area has four sides, and the hollow foil area 22 is located on one side of one of the sides.

[0060] The present application attaches the second conductive material to the surface of the active material layer, excluding the other three side walls of the active material layer except the side walls close to the empty foil area, that is, the three side walls (one is the side wall opposite to the side wall to which the second conductive material is attached, and the other two side walls are two side walls perpendicular to the side wall to which the second conductive material is attached) are not attached with the second conductive material.

[0061] The first conductive layer 2 of the present application has two opposite surfaces, each of which is divided into an active coating area 21 and an empty foil area 22, each active coating area 21 is attached with a second conductive layer 4, and the surface of the first empty foil area 221 of each empty foil area 22 is attached with a second conductive layer 4; that is, the active coating structure on both sides of the current collector surface is symmetrical and the second conductive layer structure on both sides of the current collector surface is symmetrical and the description of the electrode structure in the present application is a description of the structure on both sides of the electrode surface. The innovative structure of the present application includes coating a second conductive material on the surface of the active material layer; the electrode structure is suitable for positive electrode sheets, and can also be used for negative electrode sheets; the electrode of the present application is particularly suitable for electrodes with high surface capacity.

[0062] In order to improve the electron transfer efficiency and reduce the internal resistance, the present application extends the second conductive material from the surface of the active material layer to cover the area in the empty foil area of ​​the first conductive layer close to the active layer, and the remaining empty foil area is reserved as the pole ear connection structure. In the above-mentioned covering process, the second conductive material also covers the side wall surface of the active material layer close to the empty foil area. The covering is a process of continuous extension and covering of the second conductive layer, and does not bypass and cover the side surface in the thickness direction of the active material layer. When the second conductive material covers the front empty foil area of ​​the first conductive layer, the first conductive material and the second conductive material intersect, overlap and adhere together to form a composite conductive layer. The specific structure of the composite conductive layer is that the first conductive material is in the middle, and the second conductive material is attached on both sides. In this electrode structure, the second conductive layer 4 is composed of a second conductive layer 41 attached to the surface of the active material layer and a second conductive layer 42 attached to the surface of the first empty foil, such as Figure 2 As shown. This application can improve the conductivity by compounding the first conductive material and the second conductive material into a double-layer conductive layer in the empty foil area, thereby reducing the electrode electron transfer impedance and improving the battery power. The internal resistance of the battery using the high surface capacity double-layer conductor electrode designed in this application can be reduced to 23-34.8mΩ, the energy density can be increased to 101%-131%, and the IC charging constant current ratio can be increased to 73.8%-88.3%. The internal resistance and battery power are significantly improved.

[0063] In some embodiments, a tab connector is provided in the second hollow foil area 222. In the present invention, other hollow foil areas on the hollow foil except the area covered by the second conductive material can be used as tabs or their connection structures.

[0064] In some embodiments, the material of the first conductor is a conductive metal, that is, a current collector.

[0065] In some embodiments, the material of the second conductor is a non-metallic conductive material. The present application selects non-metallic conductive materials as the material of the second conductor, firstly to further improve the conductivity of the electrode and to have good composite properties with the first conductive material, and secondly to be suitable for forming a conductive network layer on the surface of the active material layer while also having gaps for ion transmission, that is, the second conductor material forms a porous network-like conductive layer, which improves electronic conductivity while not affecting the transmission of lithium ions.

[0066] In some embodiments, the thickness of the second conductive layer 41 attached to the surface of the active material layer 3 is 1 to 7 microns; the thickness of the second conductive layer 42 attached to the surface of the first empty foil area 221 is 1 to 10 microns; the height of the second conductive layer 42 attached to the surface of the first empty foil area 221 is 100 to 200 microns; the thickness of the first conductive layer 2 is 1 to 30 microns; and the thickness of the active material layer 3 is 30 to 100 microns.

[0067] In some embodiments, the thickness of the second conductive layer 41 attached to the surface of the active material layer 3 is 1 to 5 microns; the thickness of the second conductive layer 42 attached to the surface of the first empty foil area 221 is 5 to 10 microns; the height of the second conductive layer 42 attached to the surface of the first empty foil area 221 is 100 to 150 microns; the thickness of the first conductive layer 2 is 1 to 20 microns; and the thickness of the active material layer 3 is 50 to 65 microns.

[0068] In some embodiments, the thickness of the second conductive layer 41 attached to the surface of the active material layer 3 is 1 to 3 microns; the thickness of the second conductive layer 42 attached to the surface of the first empty foil area 221 is 5 to 8 microns; the height of the second conductive layer 42 attached to the surface of the first empty foil area 221 is 100 to 120 microns; the thickness of the first conductive layer 2 is 4 to 13 microns.

[0069] The thickness of the second conductive layer 41 attached to the active material layer of the present application and the thickness and height of the second conductive layer 42 attached to the first empty foil area are related to the surface capacity of the single-layer electrode. The above-mentioned thickness and height parameters are more suitable for electrodes with high surface capacity; wherein the high surface capacity is closely related to the thickness and surface density of the active material layer and the active material itself.

[0070] In some embodiments, the material of the first conductive layer is selected from one or more of a conductive metal, a composite of a conductive metal and a polymer, and an alloy of a conductive metal; wherein the conductive metal is selected from aluminum, copper, or nickel.

[0071] The first conductive material of the present application is also a conventional current collector material, including the material of the negative electrode or the positive electrode, and in addition, may also include other commonly used current collector materials.

[0072] In some embodiments, the material of the second conductive layer is selected from one or more of conductive carbon black (Super P), conductive graphite KS-6, multi-walled carbon nanotubes, single-walled carbon nanotubes, vapor-grown carbon fibers, graphene, and conductive carbon microspheres. The above materials are preferred because they have the advantages of firstly good conductivity, secondly, they can form a porous network structure without affecting ion conduction, and thirdly, they are easy to process. The present application preferably selects some materials with better conductivity and no side reactions with the electrolyte from the non-metallic conductive materials. Using the above materials as the second conductive material can further improve the conductivity of the electrode and reduce the internal resistance of the electrode.

[0073] In some embodiments, the active material of the active material layer includes a positive electrode active material or a negative electrode active material; the positive electrode active material includes one or more of lithium iron phosphate, lithium manganese iron phosphate, nickel cobalt manganese oxide (such as model 811), nickel cobalt aluminum manganese oxide, lithium-rich manganese and lithium manganese oxide materials; the negative electrode active material includes one or more of graphite, silicon oxygen carbon, silicon carbon and nano silicon. The intermediate layer of the electrode of the present application is an active material, which can be the above materials, or other conventionally used positive or negative electrode active materials can be selected.

[0074] In some embodiments, the electrode is a positive electrode and / or a negative electrode; the surface capacity of the positive electrode is greater than or equal to 2.0 mAh / cm 2 ; The surface capacity of the negative electrode is greater than or equal to 2.2 mAh / cm 2 ; Further preferably, the surface capacity of the positive electrode is 3.5 to 5.5 mAh / cm 2 ; The surface capacity of the negative electrode is 3.85~5.95mAh / cm 2 The dual-conductor structure designed in this application is more suitable for the above-mentioned high surface capacity electrode.

[0075] According to the second aspect of the present application, a method for preparing the above-mentioned electrode is provided, the method comprising:

[0076] Step 1: coating the electrode slurry on two opposite surfaces of the active coating area of ​​the first conductive layer respectively to form an active material layer; wherein the area on the surface of the first conductive layer not coated with the electrode slurry is a blank foil area;

[0077] Step 2: Continuously apply the second conductive paste to the surface of the active material layer away from the first conductive layer, the side wall of the active material layer close to the empty foil area, and the surface of the first empty foil area to form a second conductive layer; wherein the area in the empty foil area close to the active material layer is the first empty foil area, and the area not coated with the second conductive paste is the second empty foil area.

[0078] The method for preparing the electrode of the present application has simple operation steps and the prepared electrode structure has good quality. The internal resistance of the battery using the high surface capacity double-layer conductor electrode prepared by the present application can be reduced to 23-34.8 mΩ, the energy density can be increased to 101%-131%, and the IC charging constant current ratio can be increased to 73.8%-88.3%, and the internal resistance and battery power are significantly improved.

[0079] In the preparation method of the present application, the length and width of the second conductor layer correspond to at least the length and width of the active material layer; when applying the second conductive material, the active material layer can be applied and dried before applying the second conductive material, or the active material layer can be dried and rolled before applying the second conductive material.

[0080] According to the third aspect of the present application, a battery cell is provided, which includes a positive electrode, a negative electrode, a separator, and an electrolyte; wherein the structural design of the positive electrode and the negative electrode can adopt the electrodes of the dual conductive material designed in the present application; and the battery cell assembly method can be winding or lamination.

[0081] According to a fourth aspect of the present application, a battery is provided, comprising a battery cell, a casing, and a cover; wherein the battery cell is a battery cell assembled with electrodes of a dual conductive structure according to the present application.

[0082] In some embodiments, the working current of the battery of the present application is not less than 1C working current; that is, the current required to discharge the battery from full charge to empty at a constant current of 1 hour at room temperature is 1C current.

[0083] In some embodiments, the internal resistance of the battery of the present application is 23-35 mΩ, and the battery power is high.

[0084] According to the fifth aspect of the present application, an electrical device is provided, and the battery used in the device can adopt the battery with electrodes having a dual conductive structure assembled in the present application; for example, this battery can be used in mobile phones, computers, etc.

[0085] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0086] The raw materials used in the examples and comparative examples of the present application can all be purchased commercially.

[0087] In the embodiments and comparative examples of the present application, a battery internal resistance meter is used to test the battery internal resistance; a charge and discharge meter is used to test the battery energy density improvement rate; and a charge and discharge meter is used to test the battery 1C charging constant current ratio.

[0088] Example 1

[0089] 1) Mix lithium nickel cobalt manganese oxide with polyvinylidene fluoride glue, conductive carbon black and carbon nanotubes in a mass ratio of 95:2:1:1 to form a positive electrode slurry; according to the single-layer capacity of 3.5 mAh / cm 2 The positive electrode slurry is coated on the active coating area 21 on the two opposite surfaces of the first conductive material aluminum foil (i.e., the first conductive layer 2), dried, and rolled to form an active material layer 3 with a single-side layer thickness of 50 μm, leaving an empty foil area 22. The surface structure of the electrode piece is as follows Figure 1As shown; on the two opposite surfaces of the active material layer 3 (i.e., the two active material layers 3 on the two opposite surfaces of the aluminum foil), the second conductive material single-walled carbon nanotube slurry is coated on the surface of each of the two active material layers 3, and the coating thickness on one side is 1 μm, forming a second conductive layer 41 attached to the active material layer 3; and then continue to coat from the surface of the active material layer 3 to the two opposite surfaces of the first empty foil area 221 in the empty foil area 22 reserved by the aluminum foil, and extend the coated single-walled carbon nanotube slurry to form a second conductive layer 42 attached to the first conductive layer, and the first conductive layer and the second conductive layer are superimposed to form a composite conductive layer, as shown Figure 2 As shown; wherein, the area near the active material layer 3 in the empty foil area 22 is the first empty foil area 221, and the area not coated with the second conductive paste is the second empty foil area 222, which serves as a pole ear connection structure; the coating height (or coating length or extension height) of the single-walled carbon nanotube paste in the first empty foil area 221 is 0.1 mm, and the coating thickness is 5 μm (that is, the coating thickness of the second conductive layer 42 coated on the surface of the first empty foil area 221 is 5 μm); after drying, a double conductive positive electrode is obtained, and the surface structure of the pole piece is as shown Figure 2 As shown, the side structure of the pole piece is as follows Figure 3 As shown;

[0090] 2) The coating method of the negative electrode is the same as that of the positive electrode; the silicon oxygen carbon negative electrode material is mixed with sodium hydroxymethyl carboxylate glue, styrene butadiene rubber latex, conductive carbon black, and carbon nanotubes in a mass ratio of 94:2:2:1:1 to form a negative electrode slurry; according to the single layer capacity of 3.85mAh / cm 2 The negative electrode slurry is coated on the active coating areas on the two opposite surfaces of the copper foil, dried, and rolled to form an active material layer 3, leaving an empty foil area 22. The surface structure of the electrode sheet is as follows: Figure 1 As shown; on the two opposite surfaces of the active material layer 3, the second conductive material single-walled carbon nanotube slurry is coated on the surface of each of the two active material layers 3, and the coating thickness on one side is 1 μm, forming a second conductive layer 41 attached to the active material layer 3; and then continue to coat from the surface of the active material layer 3 to the two opposite surfaces of the first empty foil area 221 in the empty foil area 22 reserved by the aluminum foil, and extend the coated single-walled carbon nanotube slurry to form a second conductive layer 42 attached to the first conductive layer, and the first conductive layer and the second conductive layer are superimposed to form a composite conductive layer, as shown Figure 2 As shown; the area near the active material layer 3 in the empty foil area 22 is the first empty foil area 221, and the area not coated with the second conductive paste is the second empty foil area 222, which serves as the pole ear connection structure; the coating height (or called coating length or extension height) of the single-walled carbon nanotube paste in the first empty foil area 221 is 0.1mm, and the coating thickness is 5μm (that is, the coating thickness of the second conductive layer 42 coated on the surface of the first empty foil area 221 is 5μm); after drying, a double conductive positive electrode is obtained, and the surface structure of the pole piece is as shown Figure 2As shown, the side structure of the pole piece is as follows Figure 3 As shown;

[0091] 3) Forming the positive electrode sheet and the negative electrode sheet respectively, and baking at 100°C to remove water;

[0092] 4) stacking, welding and packaging the negative electrode, the electronically insulating and ion-conducting polyethylene film and the positive electrode to obtain a battery cell;

[0093] 5) Connecting the battery cell to the charge and discharge channel to activate the battery cell; the activation process used is: 0.01C constant current charging for 10 hours, 0.05C constant current charging to 4.2V, switching to constant voltage charging until the current drops to 0.02C, standing for 1 hour, and discharging at 0.1C constant current to 2.5V;

[0094] 6) The above battery is charged at 1C constant current and constant voltage, the constant current charging capacity is recorded and the constant current ratio is calculated.

[0095] 7) Charge the above battery at 1C, measure the AC impedance value and record it, see Table 1.

[0096] Example 2

[0097] The difference between Example 2 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0098] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated, and the single-side thickness is 52 μm. The second conductive material is a multi-walled carbon nanotube slurry, and the coating thickness on the active material layer is 1 μm. The coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm. A positive electrode is obtained, and the structure is as follows: Figure 2 and Figure 3 ;

[0099] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated with a single-side thickness of 52 μm, the second conductive material is a multi-walled carbon nanotube slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0100] Assemble the battery cells and test the performance as shown in Table 1.

[0101] Example 3

[0102] The difference between Example 3 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0103] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated with a single-side thickness of 52 μm, the second conductive material is a vapor-grown carbon fiber slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a positive electrode with a structure as shown Figure 2 and Figure 3 ;

[0104] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated with a single-side thickness of 53 μm, the second conductive material is a vapor-grown carbon fiber slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0105] Assemble the battery cells and test the performance as shown in Table 1.

[0106] Example 4

[0107] The difference between Example 4 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0108] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated with a single-side thickness of 52 μm, the second conductive material is a graphene slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a positive electrode with a structure as shown Figure 2 and Figure 3 ;

[0109] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated with a single-side thickness of 53 μm, the second conductive material is a graphene slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0110] Assemble the battery cells and test the performance as shown in Table 1.

[0111] Example 5

[0112] The difference between Example 5 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0113] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated with a single-side thickness of 52 μm, the second conductive material is Super P slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a positive electrode with a structure as shown Figure 2 and Figure 3 ;

[0114] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated with a single-side thickness of 53 μm, the second conductive material is Super P slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0115] Assemble the battery cells and test the performance as shown in Table 1.

[0116] Example 6

[0117] The difference between Example 6 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0118] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated with a single-side thickness of 52 μm, the second conductive material is KS-6 slurry, the coating thickness on the active material layer is 7 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 10 μm, to obtain a positive electrode with a structure as shown Figure 2 and Figure 3 ;

[0119] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated with a single-side thickness of 53 μm, the second conductive material is KS-6 slurry, the coating thickness on the active material layer is 7 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 10 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0120] Assemble the battery cells and test the performance as shown in Table 1.

[0121] Example 7

[0122] The difference between Example 7 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0123] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated, and the single-side thickness is 55 μm; the second conductive material is a composite slurry of Super P and single-walled carbon nanotubes (weight ratio 10:1), and the coating thickness on the active material layer is 1 μm; the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm; a positive electrode is obtained, and the structure is as follows Figure 2 and Figure 3 ;

[0124] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated with a single-side thickness of 55 μm; the second conductive material is a composite slurry of Super P and single-walled carbon nanotubes (weight ratio 10:1), the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0125] Assemble the battery cells and test the performance as shown in Table 1.

[0126] Example 8

[0127] The difference between Example 8 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0128] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated, and the single-side thickness is 55 μm. The second conductive material is a composite slurry of KS-6 and single-walled carbon nanotubes (weight ratio 10:1), and the coating thickness on the active material layer is 7 μm; the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 10 μm; a positive electrode is obtained, and the structure is as follows Figure 2 and Figure 3 ;

[0129] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2The active material layer is coated with a single-side thickness of 55 μm, the second conductive material is a composite slurry of KS-6 and single-walled carbon nanotubes (weight ratio 10:1), the coating thickness on the active material layer is 7 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 10 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0130] Assemble the battery cells and test the performance as shown in Table 1.

[0131] Example 9

[0132] The difference between Example 9 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0133] Specifically: According to the single-layer positive electrode surface capacity of 2.0mAh / cm 2 The active material layer is coated, and the single-side thickness is 55 μm. The second conductive material is a single-walled carbon nanotube slurry, and the coating thickness on the active material layer is 1 μm. The coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm. A positive electrode is obtained, and the structure is as follows Figure 2 and Figure 3 ;

[0134] According to the single-layer negative electrode surface capacity of 2.2 mAh / cm 2 The active material layer is coated with a single-side thickness of 55 μm, the second conductive material is a single-walled carbon nanotube slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0135] Assemble the battery cells and test the performance as shown in Table 1.

[0136] Example 10

[0137] The difference between Example 10 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0138] Specifically: According to the single-layer positive electrode surface capacity of 4.4mAh / cm 2 The active material layer is coated, and the single-side thickness is 55 μm. The second conductive material is a single-walled carbon nanotube slurry, and the coating thickness on the active material layer is 1 μm. The coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm. A positive electrode is obtained, and the structure is as follows Figure 2 and Figure 3 ;

[0139] According to the single-layer negative electrode surface capacity of 2.2 mAh / cm 2 The active material layer is coated with a single-side thickness of 55 μm, the second conductive material is a single-walled carbon nanotube slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0140] Assemble the battery cells and test the performance as shown in Table 1.

[0141] Embodiment 11

[0142] The difference between Example 11 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0143] Specifically: According to the single-layer positive electrode surface capacity of 5.5mAh / cm 2 The active material layer is coated, and the single-side thickness is 55 μm. The second conductive material is a single-walled carbon nanotube slurry, and the coating thickness on the active material layer is 1 μm. The coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm. A positive electrode is obtained, and the structure is as follows Figure 2 and Figure 3 ;

[0144] According to the single-layer negative electrode surface capacity of 5.95mAh / cm 2 The active material layer is coated with a single-side thickness of 55 μm, the second conductive material is a single-walled carbon nanotube slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0145] Assemble the battery cells and test the performance as shown in Table 1.

[0146] Example 12

[0147] The difference between Example 12 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0148] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated, and the single-side thickness is 55 μm. The second conductive material is a single-walled carbon nanotube slurry, and the coating thickness on the active material layer is 1 μm. The coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 1 μm. A positive electrode is obtained, and the structure is as follows Figure 2 and Figure 3 ;

[0149] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated with a single-side thickness of 55 μm, the second conductive material is a single-walled carbon nanotube slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 1 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0150] Assemble the battery cells and test the performance as shown in Table 1.

[0151] Example 13

[0152] The difference between Example 13 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0153] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated, and the single-side thickness is 55 μm. The second conductive material is a single-walled carbon nanotube slurry, and the coating thickness on the active material layer is 2 μm. The coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 2 μm. A positive electrode is obtained, and the structure is as follows Figure 2 and Figure 3 ;

[0154] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated with a single-side thickness of 55 μm, the second conductive material is a single-walled carbon nanotube slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 2 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0155] Assemble the battery cells and test the performance as shown in Table 1.

[0156] Embodiment 14

[0157] The difference between Example 14 and Example 1 is that the positive electrode, negative electrode surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0158] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2The active material layer is coated, and the single-side thickness is 55 μm. The second conductive material is a single-walled carbon nanotube slurry, and the coating thickness on the active material layer is 1 μm. The coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 8 μm. A positive electrode is obtained, and the structure is as follows Figure 2 and Figure 3 ;

[0159] According to the single-layer negative electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated with a single-side thickness of 55 μm, the second conductive material is a single-walled carbon nanotube slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 8 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0160] Assemble the battery cells and test the performance as shown in Table 1.

[0161] Embodiment 15

[0162] The difference between Example 15 and Example 1 is that the positive electrode, negative electrode slurry, surface capacity, second conductive material, layer thickness, coating length, etc. are different;

[0163] Specifically, lithium nickel cobalt manganese oxide is mixed with polytetrafluoroethylene, carbon nanotubes, and electrolyte in a mass ratio of 60:5:5:30 to form a positive electrode slurry; according to the single-layer positive electrode surface capacity of 3.5 mAh / cm 2 The active material layer is coated, and the single-side thickness is 55 μm. The second conductive material is a single-walled carbon nanotube slurry, and the coating thickness on the active material layer is 1 μm. The coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm. A positive electrode is obtained, and the structure is as follows Figure 2 and Figure 3 ;

[0164] The silicon-oxygen-carbon negative electrode material was mixed with styrene-butadiene rubber latex, carbon nanotubes and electrolyte in a mass ratio of 60:5:5:30. The single-layer negative electrode surface capacity was 3.85 mAh / cm 2 The active material layer is coated with a single-side thickness of 55 μm, the second conductive material is a single-walled carbon nanotube slurry, the coating thickness on the active material layer is 1 μm, the coating length (or extension height) of the first empty foil area in the empty foil area is 0.1 mm, and the single-side coating thickness is 5 μm, to obtain a negative electrode with a structure as shown Figure 2 and Figure 3 ;

[0165] Assemble the battery cells and test the performance as shown in Table 1.

[0166] Comparative Example 1

[0167] The difference between Comparative Example 1 and Example 1 is that the positive and negative electrode sheets of Comparative Example 1 are of conventional structure, and the two opposite surfaces of the current collector are coated with active materials; the second conductive material is not used, and the structure is as follows Figure 4 ; Assemble the battery cells and test the performance as shown in Table 1.

[0168] Comparative Example 2

[0169] The difference between Comparative Example 2 and Example 1 is that the electrode slurry, surface capacity, and coating are different;

[0170] Specifically, lithium nickel cobalt manganese oxide, polyvinylidene fluoride glue and conductive carbon black are mixed in a mass ratio of 96:2:2 to form a first positive electrode slurry; a single-layer positive electrode surface capacity of 1.75 mAh / cm 2 The first active material layer is coated with a single-side thickness of 40 μm, dried, and rolled, and then lithium nickel cobalt manganese oxide, polyvinylidene fluoride glue, and carbon nanotubes are mixed in a mass ratio of 97:2:1 to form a second positive electrode slurry; and then the single-side surface capacity is 1.75 mAh / cm 2 Apply the second active material layer with a single-side thickness of 15 μm, dry it, and roll it to form a positive electrode sheet;

[0171] The silicon-oxygen-carbon negative electrode material was mixed with sodium hydroxymethylcarboxylate, styrene-butadiene rubber latex, conductive carbon black and carbon nanotubes in a mass ratio of 94:2:2:1:1. 2 Apply active material layer, with a thickness of 55 μm on one side, to the negative electrode;

[0172] Assemble the battery cells and test the performance as shown in Table 1.

[0173] Comparative Example 3

[0174] The difference between Comparative Example 3 and Example 1 is that the electrode slurry, surface capacity, and coating are different;

[0175] Specifically, single-crystal lithium nickel cobalt manganese oxide, polyvinylidene fluoride glue and conductive carbon black are mixed in a mass ratio of 96:2:2 to form a first positive electrode slurry; a single-layer positive electrode surface capacity of 1.75 mAh / cm 2 The first active material layer is coated with a single-side thickness of 40 μm, dried, and rolled. Then, polycrystalline nickel cobalt lithium manganese oxide material is mixed with polyvinylidene fluoride glue and carbon nanotubes in a mass ratio of 96:2:2 to form the second positive electrode slurry. Then, the single-side surface capacity is 1.75 mAh / cm 2 Apply the second active material layer with a single-side thickness of 15 μm, dry it, and roll it to form a positive electrode sheet;

[0176] The silicon oxygen carbon negative electrode material is mixed with sodium hydroxymethyl carboxylate glue, styrene butadiene rubber latex, conductive carbon black, and carbon nanotubes in a mass ratio of 94:2:2:1:1 to form a negative electrode slurry; according to the single-layer negative electrode surface capacity of 3.85 mAh / cm 2 Apply the active material layer with a single-side thickness of 55 μm to the negative electrode sheet; assemble the battery cell, and test the performance as shown in Table 1.

[0177] Comparative Example 4

[0178] The difference between Comparative Example 4 and Example 9 is that the electrode slurry, surface capacity, and coating are different;

[0179] Specifically: According to the single-layer positive electrode surface capacity of 2.0mAh / cm 2 Applying an active material layer with a single-side thickness of 55 μm; not applying a second conductive material; drying and rolling to obtain a positive electrode sheet;

[0180] According to the single-layer negative electrode surface capacity of 2.2 mAh / cm 2 The active material layer was coated with a single-side thickness of 55 μm; the second conductive material was not coated; the negative electrode sheet was obtained by drying and rolling; the battery cell was assembled, and the test performance was shown in Table 1.

[0181] Comparative Example 5

[0182] The difference between Comparative Example 5 and Example 1 is that the electrode slurry, surface capacity, and coating are different;

[0183] Specifically: According to the single-layer positive electrode surface capacity of 3.5mAh / cm 2 The active material layer is coated, dried, and rolled to form an active material layer with a single-side layer thickness of 50 μm, leaving an empty foil area; the second conductive material single-walled carbon nanotube slurry is coated on the surface of each of the two active material layers with a single-side surface coating thickness of 1 μm; the second conductive material is not coated on the empty foil area, and only the active material layer is coated to obtain a positive electrode sheet. The results are as follows Figure 5 ;

[0184] According to the single-layer positive electrode surface capacity of 3.85mAh / cm 2 The active material layer is coated, dried, and rolled to form an active material layer with a single-side layer thickness of 50 μm, leaving an empty foil area; the second conductive material single-walled carbon nanotube slurry is coated on the surface of each of the two active material layers with a single-side surface coating thickness of 1 μm; the second conductive material is not coated on the empty foil area, and only the active material layer is coated to obtain a negative electrode sheet with a structure as shown in FIG. Figure 5 ; Assemble the battery cells and test the performance as shown in Table 1.

[0185] Comparative Example 6

[0186] The difference between Comparative Example 6 and Example 15 is that the electrode slurry, surface capacity, and coating are different;

[0187] Specifically, lithium nickel cobalt manganese oxide is mixed with polytetrafluoroethylene, carbon nanotubes, and electrolyte in a mass ratio of 60:5:5:30 to form a positive electrode slurry; according to the single-layer positive electrode surface capacity of 3.5 mAh / cm 2 Apply an active material layer with a thickness of 55 μm on one side, dry and roll-press to obtain a positive electrode sheet;

[0188] The silicon-oxygen-carbon negative electrode material was mixed with styrene-butadiene rubber latex, carbon nanotubes and electrolyte in a mass ratio of 60:5:5:30. The single-layer negative electrode surface capacity was 3.85 mAh / cm 2 The active material layer was coated with a single-side thickness of 55 μm, dried and rolled to obtain the negative electrode sheet; the battery cell was assembled, and the test performance was shown in Table 1.

[0189] The performance of the cells assembled in Examples 1 to 15 and Comparative Examples 1 to 6 was tested, and the results are shown in Table 1.

[0190] Table 1

[0191]

[0192]

[0193] Note: Thickness 1 is the coating thickness of the second conductive material on the surface of the active material layer; Thickness 2 is the coating thickness of the second conductive material on the surface of the first empty foil area.

[0194] The performance test results in Table 1 show that the surface capacity of the dual positive electrode sheets in Examples 1 to 15 of the present application is 2.0 to 5.5 mAh / cm 2 The surface capacity of the negative electrode is 2.2~5.95mAh / cm 2 The internal resistance of the battery using the double conductive electrode designed in the present application can be reduced to 23-34.8 mΩ, the energy density can be increased to 101%-131%, and the IC charging constant current ratio can be increased to 73.8%-88.3%. The internal resistance of the battery in comparative examples 1-6 is 24.5-57.5 mΩ, the energy density is 100%-108%, and the 1C charging constant current ratio is 61.2%-85.7%. By comparison, it can be seen that the present application reduces the internal resistance to 60% of the original value by coating the second conductive material on the active material layer and the empty foil area, increases the energy density by 20%, and increases the 1C charging constant current ratio by 10%. The above fully proves that the double conductive layer electrode designed in the present application can significantly reduce the internal resistance of the battery and increase the battery power.

[0195] In Examples 1 to 5, Example 7, Examples 9 to 11, and Example 14, the thickness 1 of the second conductive layer in the electrode is 1 micron, the thickness 2 is 5 microns, the internal resistance of the obtained battery is between 20 and 30 mΩ, most of which are concentrated between 25 and 28, the energy density improvement rate is concentrated between 115 and 131, and the charging constant current ratio is about 85% on average; this indicates that when the coating thickness of the second conductive material on the surface of the active material layer is controlled to be less than 3 microns, preferably 1 micron, and the coating thickness of the second conductive material in the empty foil area is controlled to be more than 5 microns and the coating length is more than 0.1 mm, it is more conducive to reducing the internal resistance of the battery, improving the energy density and the charging constant current ratio.

[0196] Compared with Example 1, that is, compared with the conventional electrode structure, the present application reduces the internal resistance of the battery in Example 1 from 57.5 to 23.3, and increases the energy density from 100% to 125% by coating the second conductive material on the active layer and the empty foil layer; the 1C charging constant current ratio is increased from 61.2% to 88.3%, and the improvement effect is very obvious.

[0197] Compared with Example 1 and Comparative Example 5, although the second conductive material is also coated on the active layer of Comparative Example 5, it is not coated on the empty foil area, and the electron transmission capacity of the first conductive material electrode ear area cannot be enhanced, which is not conducive to electron transmission; Example 1 of the present application reduces the internal resistance of Comparative Example 5 from 36.3 to 23.3, increases the energy density from 101% to 125%, and increases the 1C charging constant current ratio from 68.7% to 88.3%, and the improvements in many aspects are quite obvious.

[0198] The active slurry of Example 15 adds a solid electrolyte, which itself will increase the internal resistance of the battery. On the basis of the same active material layer, Example 15 is coated with a second conductive material, while Comparative Example 6 is not coated. Compared with the two, Example 15 of the present application reduces the internal resistance of the battery of Comparative Example 6 from 100.7 to 79.8, increases the energy density from 100% to 110%, and increases the 1C charging constant current ratio from 46.6% to 63.3% by designing a dual conductive structure, with significant improvement effect.

[0199] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0200] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An electrode, characterized in that: The electrode comprises: a first conductive layer, an active material layer and a second conductive layer, wherein the active material layer is sandwiched between the first conductive layer and the second conductive layer; the surface of the first conductive layer is divided into an active coating area and a hollow foil area adjacent to one side of the active coating area; the active material layer is attached to two opposite surfaces of the active coating area respectively; The empty foil area is divided into a first empty foil area close to the active material layer and a second empty foil area away from the active material layer; the second conductive layer is continuously attached to the surface of the active material layer away from the first conductive layer, the side wall of the active material layer close to the empty foil area and the surface of the first empty foil area.

2. The electrode according to claim 1, characterized in that The material of the first conductive layer is a conductive metal; And / or, the material of the second conductive layer is a non-metallic conductive material; And / or, the second empty foil area is a tab connection area; And / or, the outer contours of the first conductive layer, the active material layer, the second conductive layer, and the empty foil area are in a square shape; And / or, a vertical connection line between two opposite sides of the first conductive layer divides the surface area of ​​the first conductive layer into the active coating area and the empty foil area.

3. The electrode according to claim 1 or 2, characterized in that The thickness of the second conductive layer attached to the surface of the active material layer is 1 to 7 microns; and / or, the thickness of the second conductive layer attached to the surface of the first empty foil area is 1 to 10 microns; and / or, the height of the second conductive layer attached to the surface of the first empty foil area is 100 to 200 microns; and / or, the thickness of the first conductive layer is 1 to 30 micrometers; And / or, the thickness of the active material layer is 30 to 100 micrometers.

4. The electrode according to claim 1 or 2, characterized in that: The thickness of the second conductive layer attached to the surface of the active material layer is 1 to 5 microns; and / or, the thickness of the second conductive layer attached to the surface of the first empty foil area is 5 to 10 microns; and / or, the height of the second conductive layer attached to the surface of the first empty foil area is 100 to 150 microns; and / or, the thickness of the first conductive layer is 1 to 20 microns; And / or, the active material layer has a thickness of 50 to 65 micrometers.

5. The electrode according to claim 1 or 2, characterized in that: The thickness of the second conductive layer attached to the surface of the active material layer is 1 to 3 microns; and / or, the thickness of the second conductive layer attached to the surface of the first empty foil area is 5 to 8 microns; and / or, the height of the second conductive layer attached to the surface of the first empty foil area is 100 to 120 microns; And / or, the thickness of the first conductive layer is 4-13 microns.

6. The electrode according to claim 1 or 2, characterized in that: The material of the first conductive layer is selected from one or more of a conductive metal, a composite of a conductive metal and a polymer, and an alloy of a conductive metal; wherein the conductive metal is selected from aluminum, copper, or nickel; And / or, the material of the second conductive layer is selected from one or more of conductive carbon black, conductive graphite, multi-walled carbon nanotubes, single-walled carbon nanotubes, vapor-grown carbon fibers, graphene, and conductive carbon microspheres; And / or, the active material of the active material layer includes a positive electrode active material or a negative electrode active material; the positive electrode active material is selected from one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, nickel cobalt aluminum manganese oxide, lithium-rich manganese and lithium manganese oxide materials; the negative electrode active material is selected from one or more of graphite, silicon oxygen carbon, silicon carbon and nano silicon.

7. The electrode according to claim 1 or 2, characterized in that: The electrode is a positive electrode and / or a negative electrode; the surface capacity of the positive electrode is greater than or equal to 2.0 mAh / cm 2 The surface capacity of the negative electrode is greater than or equal to 2.2 mAh / cm 2 .

8. The electrode according to claim 1 or 2, characterized in that: The electrode is a positive electrode and / or a negative electrode; the surface capacity of the positive electrode is 3.5 to 5.5 mAh / cm 2 The surface capacity of the negative electrode is 3.85 to 5.95 mAh / cm 2 .

9. The method for preparing an electrode according to any one of claims 1 to 8, characterized in that: The method comprises: Step 1: applying the electrode slurry to two opposite surfaces of the active coating area of ​​the first conductive layer respectively to form an active material layer; wherein the area on the surface of the first conductive layer not coated with the electrode slurry is a blank foil area; Step 2: Continuously apply the second conductive paste to the surface of the active material layer away from the first conductive layer, the side wall of the active material layer close to the empty foil area, and the surface of the first empty foil area to form a second conductive layer; wherein the area of ​​the empty foil area close to the active material layer is the first empty foil area, and the area not coated with the second conductive paste is the second empty foil area.

10. A battery, characterized in that: The electrode of the battery is the electrode according to any one of claims 1 to 8 or the electrode obtained by the preparation method according to claim 9.